Economists and Development: Rediscovering Old Truths - Enke, Stephen (Journal of Economic Literature, 2016)
A SPATE OF economic literature appeared in the late 'fifties and early 'sixties as the advanced nations' governments and economists turned their attention to the so-called developing nations. A recent survey of subsequent contributions to the theory and practice of reveals less that is new and important. Meanwhile poverty persists in the less developed countries (LDCs). And economists are realizing that several social sciences are involved. What else has been discovered or relearned during the decade of development now drawing to its close?'